Analisis Fenomena Defisit Anggaran dan Defisit Transaksi Berjalan di Indonesia - Tri Yuliana Putri; Marselina; Neli Aida (BULLET : Jurnal Multidisiplin Ilmu, 2023)
A budget deficit occurs because the fund spent by the government to develop the economu are more than the income earned. Meanwhile, the current account deficit occurs because incoming imports are more than outgoing exports so that the country lack income against foreign exchange. This research will examine the effect of the Current Account Deficit, Inflation, Exchange Rate, and Economic Growth on the Budget Deficit in Indonesia. This research is quantitative descriptive analysis using time series data used in the 2006-2019 period. The method used in Error Correction Model (ECM) to test short-term effects and Ordinary Least Square (OLS) to test long-term effects. The result of this research are indicate the result of Current Account Deficit, Inflation, Exchange Rate, and Economic Growth have a positive and significant effect on the Budget Deficit in Indonesia for the period 2006-2019.